10 Bioarchaeological Perspectives on the Materiality of Everyday Life Activities. Issue 1 (September 2015) - Wesp, Julie K.; Overholtzer, Lisa; Robin, Cynthia
ABSTRACT The activities of everyday life influence not only the extrasomatic material world, but also the material properties of our own bodies. Living bone tissue is a dynamic material that responds to external and internal stimuli to alter its size, shape, and structure, and the repetitive actions from daily life performances leave traces that can be interpreted from archaeological skeletal remains. This chapter examines how the human body can be interpreted as a type of material object that both shapes and is shaped by our behavior. These changes are highlighted through the examination of a small skeletal population from the Postclassic site of Xaltocan in Central Mexico. Bioarchaeological analyses of these material changes add a unique perspective to the discussion of the materiality of everyday life in the past.